Ukraine : 2004 Article IV Consultation-Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2005)
This 2004 Article IV Consultation highlights that six years after the 1998 financial crisis, Ukraine continues to recover strongly. In 2003, real GDP grew by 9.4 percent, despite a poor harvest, and reached 13.5 percent through July 2004. Growth in 2003-04 has been prompted by favorable external demand, a competitive cost structure, and dynamic domestic demand. Inflation has been moderate, but strong upward pressures are emerging. There has been progress in the structural reform agenda, but tax administration should improve.